Morphological and genetic characterization of the sharpsnout seabream populations (Diplodus puntazzo, Sparidae) along a boundary area between the two Mediterranean basins. Issue 8 (13th September 2016) - Hammami, Ibtissem; Ben Hassine, Oum Kalthoum; Kaouèche, Myriam; Bahri-Sfar, Lilia
ABSTRACT: In order to test the potential ecological role of the Siculo-Tunisian Strait as a geographic barrier, the morphological and genetic variation of eight Tunisian samples of the sharpsnout seabream, Diplodus puntazzo, were studied, based on 23 truss network elements and 13 polymorphic allozyme loci. Significant morphological differences were observed between studied samples, especially between lagoon ones. Although genetic data did not support the detected morphometric variation, F -statistics indices ( F IS and F ST ) revealed a significant departure from panmixia with heterozygote deficiencies and slight genetic differentiation between samples. Genetic results suggested the existence of moderate and local genetic heterogeneity that can be explained by the chaotic genetic patchiness hypothesis. Morphological and genetic results showed that the Siculo-Tunisian Strait does not seem to act as a barrier limiting the connectivity between the natural populations of D. puntazzo, at least at the scale of the Tunisian coast. Thus, the phenotypic variation identified in this study appears to be environmentally induced through the exploitation of different ecological niches and hydrodynamic constraints.